On Thin Ice : How Cutting Pollution Can Slow Warming and Save Lives - World Bank; International Cryosphere Climate Initiative (World Bank, Washington, DC, 2014)
Climate change is happening faster and in a dramatically more visible way in the Earth's cryosphere than anywhere else on earth. Cryosphere is defined as elements of the Earth system containing water in its frozen state. The average temperature has risen here at over twice the global mean in the Arctic, Antarctic Peninsula, and much of the Himalayas and other mountain regions. This report summarizes the changes already being observed in the following five major cryosphere regions: the Andes, Antarctica, Arctic, East African Highlands, and the Himalayas. It then provides a science-based assessment of the impact of addressing methane and black carbon to reduce the risk to the global environment and human societies, especially for the most vulnerable populations. Chapter 2 provides a comprehensive assessment of the changes occurring in these five regions, based on the most recent literature, including the Fifth Assessment Report of the Intergovernmental Panel on Climate Change (2013). Chapter 3 describes the pollution and climate nexus and the evolving knowledge of how methane and black carbon impact climate specifically in cryosphere regions. Chapter 4 presents the background and methods used for new modeling work conducted as part of this study, building extensively the United Nations Environment Programme/World Meteorological Organization Integrated Assessment of Black Carbon and Ozone (2010). Chapter 5 presents the results of the new modeling in these five major cryosphere regions as well as globally for health, crop impacts, and climate. Finally, Chapter 6 discusses the implications and new directions for the cryosphere regions emerging from these modeling results.